Embedding value-based organization: An identification of critical success factors and challenges - Olli-Pekka Viinamäki (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
The recent discourse on modernizing organizations and leadership has often placed a strong emphasis on values and ethics. This article elaborates on the benefits and challenges in the integration of values into leadership and organizational actions, most notably in regards to appraisals of values-based leadership (VBL). It is proposed that if the critical success factors and the challenges in implementing value-based organization are not identified, this would lead to unintended consequences in organizations, such as insignificant value-statements, inappropriate use of values, and illegitimate leadership practices. The discussion deals with intra-organizational leadership prospects and challenges, namely changes in organizational structures and authority, participation, communication, image and perceptions, and the integration of values.
Keywords: 650; Value-based organization; Values; organization; leadership; ethics; values-based leadership; organizational values; organizational culture